Peningkatan Keterampilan Passing Bawah, Passing Atas, Dan Smash Melalui Metode Bermain Pada Ekstrakurikuler Bola Voli Putra SMP Negeri 2 Pakisaji - Rizal Asista Ramadhani; Agus Tomi; Dona Sandy Yudasmara (LPPM Politeknik Pratama, 2023)
This research was motivated by a problem in the form of a decrease in the basic volleyball extracurricular technical skills for men's volleyball at SMP Negeri 2 Pakisaji, so the researchers tried to apply playing methods to improve basic volleyball technical skills at SMP Negeri 2 Pakisaji. This study aims to determine whether the playing method can improve the basic technical skills of underpassing, overpassing and smash. The research method used was sports action research (PTO) which was carried out over 2 cycles with 9 meetings in each cycle. Each cycle contains planning, action, observation and reflection. The research subjects were 15 male volleyball extracurricular participants. The research instruments used were tests and non-tests in the form of observations, interviews and documentation. This research uses quantitative descriptive data analysis techniques. The results of research on assessing bottom passing ability obtained a comparison of improvement between cycle 1 and cycle 2 of 17%. Meanwhile, the results of the upper passing ability assessment obtained a comparison of improvement between cycle 1 and cycle 2 of 15%. Furthermore, the results of the smash ability assessment obtained a comparison of the increase between cycle 1 and cycle 2 of 21%. It can be concluded that the playing method is able to improve students' basic volleyball technical skills after implementing training for 2 cycles.